The artisan's wife - Miller, Judith, 1944- (Miller, Judith, 1944- Refined by love., 2016)
Ainslee McKay's world is upended when her twin sister secretly elopes and leaves Ainslee alone to move to Weston, West Virginia, to fulfill their obligation at the McKay family's new tile works. While her brother, Ewan, agrees to travel with her and help her learn the ropes, she still intends to sell this business she no longer wants if a buyer can be found. When the talented Levi Judson arrives to show Ainslee his designs for new tiles, she's impressed by his skill and passion for the business but feels she must keep her true plans for the business a secret from him. And though Levi hopes for a long, successful career at McKay Tile Works, he's hiding his true reason for coming to Weston. Can the growing feelings between them survive if the truth comes to light---or is a future together as uncertain as the future of the tile works itself?